What happens when performance‐based financing meets free healthcare?: Evidence from an interrupted time‐series analysis - Kuunibe, Naasegnibe; Lohmann, Julia; Hillebrecht, Michael; Nguyen, Hoa Thi; Tougri, Gauthier; De Allegri, Manuela (Health policy and planning, 2020)
In spite of the wide attention performance-based financing (PBF) has received over the past decade, no evidence is available on its impacts on quantity and mix of service provision nor on its interaction with parallel health financing interventions. Our study aimed to examine the PBF impact on quantity and mix of service provision in Burkina Faso, while accounting for the parallel introduction of a free healthcare policy. We used Health Management Information System data from 838 primary-level health facilities across 24 districts and relied on an interrupted time-series analysis with independent controls. We placed two interruptions, one to account for PBF and one to account for the free healthcare policy. In the period before the free healthcare policy, PBF produced significant but modest increases across a wide range of maternal and child services, but a significant decrease in child immunization coverage. In the period after the introduction of the free healthcare policy, PBF did not affect service provision in intervention compared with control facilities, possibly indicating a saturation effect. Our findings indicate that PBF can produce modest increases in service provision, without altering the overall service mix. Our findings, however, also indicate that the introduction of other health financing reforms can quickly crowd out the effects produced by PBF. Further qualitative research is required to understand what factors allow healthcare providers to increase the provision of some, but not all services and how they react to the joint implementation of PBF and free health care.
Gesehen am 04.01.2021